Our Lady of Krasno: the Shrine and its Inventory as Witnesses of the Healing Practicies - Belaj, Marijana (2007)
Religious practicies related to the belief in patron saints has in its core a notion of the saints' influence on earthly needs, mostly on protection and help with diseases. In moments of uncertainty there is a tendency to achieve a direct, unrestrained and close communication with the saint, which also frequently includes some material traces – reminders and witnesses of that communication. Since there is a belief that the communication can easily be achieved at the shrine, shrines turn out to be stages of materialized hopes directed towards healing, and of the gratitude for the gained health. That is the frame within which the shrine of Our Lady of Krasno is observed in this paper. The variety of objects – material witnesses of the communication with the supernatural at the moments of disease is pointed out (jewellery, rosaries, votives, written notes, photographs and so on), as well as the role of the shrine, equipped with these objects, mediating the need to acquire the bodily and spiritual integrity. In relation to the latter, the suggestibility and genuineness exhibited at the shrine are also discussed.